Development of prototype of electronic speckle interferometry based spirometer. (January 2021) - Arun Kumar, R; Sunil Kumar, R; Sreejyothi, S; Raj, Vimal; Swapna, M S; Sankararaman, S.
Highlights: Development of prototype of electronic speckle interferometric spirometer (ESPIS). Development of a Diaphragm - Nozzle - Mouth piece (DNM) module for ESPIS. Low-cost and sensitive spirometer for biomedical applications. Abstract: The paper reports the design, construction, and calibration of the prototype of a spirometer based on electronic speckle interferometry (ESPI). The conventional ESPI setup is modified by incorporating a DNM (Diaphragm-Nozzle-Mouthpiece) module comprising a metallic diaphragm, regulated airflow channel, and a mouthpiece. The exhaled air after a deep breathe is channelled to the DNM module where the diaphragm gets deformed. From the circular fringe pattern obtained by subtracting the speckled images before and after deformation of the metallic diaphragm, the radius of curvature (R) due to deformation is calculated using the principle of Newton's rings. The value of R and peak expiratory flow rate (PEFR) from the standard spirometer reading are correlated. From the 640 observations spread over the range 100 - 500 L/min in the standard spirometer, an empirical relation is set in terms of R from the scatter plot. The ESPI spirometer (ESPIS) is validated by determining the value of R corresponding to a particular PEFR from the empirical relation and also from the standard spirometer. The PEFR calculated from ESPIS matches well with the standard spirometer reading, which suggests that the system designed and constructed can be used for biomedical applications for assessing lungs' efficiency.